Structural change and fiscal flows: a framework for analyzing the effects of urban events - Ruhil, Anirudh V.S. (2003)
The political and policy impacts of alternative governing arrangements are an enduring and important puzzle of urban politics. Locating the source of the empirical confusion over structural effects in the use of state data analysis, the author emphasizes the benefits of investigating the substantive consequences of identifiable events (e.g. changes in form of government, budgeting techniques, the election of a minority mayor) via dynamic multiwave panel data and appropriate estimation techniques. The point is illustrated by analyzing the fiscal effects of reformism in a panel of 222 cities (1946-1966). Findings suggest no more than transient decreases in per-capita city expenditures postadoption of council-manager government. - Reproduced.
Keywords: Local government